The United States Holocaust Memorial Museum Encyclopedia of Camps and Ghettos, 1933-1945, Volume II : Ghettos in German-Occupied Eastern Europe - Hecker, Melvin, 1946-; Dean, Martin, 1962-; United States Holocaust Memorial Museum (Book collections on Project MUSE., 2012)
Offers a comprehensive account of how the Nazis conducted the Holocaust throughout the scattered towns and villages of Poland and the Soviet Union. It covers numerous sites, including both open and closed ghettos. Regional essays outline the patterns of ghettoization in 19 German administrative regions.